International corporations in the age of the global Internet – new normality or a harbinger of a crisis? - Sędkowski, Michał (Koszty współczesnych kryzysów, 2021)
For many years, social media has offered free space for any user-created content, but only recently have questions been asked about the actual cost of using these services. Thanks to Internet technologies, the activity of users on the Internet is tracked and processed for marketing purposes, very often without the possibility of stopping or limiting this process. This problem turned out to be particularly important during the pandemic, where the Internet became the only source of information and a tool for communication with others. The author of the article puts forward a research hypothesis that users have a very limited scope of control over their data on the Internet, and state agencies do not have the appropriate tools to force a real change in this regard. The conducted analysis of sources confirmed this hypothesis, pointing to a weakness of the European Union and the United States in terms of real impact on global corporations.